High-performance fiber strain sensor of carbon nanotube/thermoplastic polyurethane@styrene butadiene styrene with a double percolated structure - XIANG, Dong; LIU, Libing; CHEN, Xiaoyu; WU, Yuanpeng; WANG, Menghan; ZHANG, Jie; ZHAO, Chunxia; LI, Hui; LI, Zhenyu; WANG, Ping; LI, Yuntao (Frontiers of materials science, 2022)
In this work, a high-performance fiber strain sensor is fabricated by constructing a double percolated structure, consisting of carbon nanotube (CNT)/thermoplastic polyurethane (TPU) continuous phase and styrene butadiene styrene (SBS) phase, incompatible with TPU (CNT/TPU@SBS). Compared with other similar fiber strain sensor systems without double percolated structure, the CNT/TPU@SBS sensor achieves a lower percolation threshold (0.38 wt.%) and higher electrical conductivity. The conductivity of 1%-CNT/TPU@SBS (4.12×10 −3 S·m −1) is two orders of magnitude higher than that of 1%-CNT/TPU (3.17×10 −5 S·m −1) at the same CNT loading of 1 wt.%. Due to double percolated structure, the 1%-CNT/TPU@SBS sensor exhibits a wide strain detection range (0.2%-100%) and an ultra-high sensitivity (maximum gauge factor (GF) is 32411 at 100% strain). Besides, the 1%-CNT/TPU@SBS sensor shows a high linearity ( R 2 = 0.97) at 0%-20% strain, relatively fast response time (214 ms), and stability (500 loading/unloading cycles). The designed sensor can efficiently monitor physiological signals and movements and identify load distribution after being woven into a sensor array, showing broad application prospects in wearable electronics.